Sensitivity of GNSS blind interference detection algorithm based on fourth-order autocumulants - Sousa, Fernando (2019)
GNSS signals affected by additive channel noise are approximately Gaussian but often the presence of interference may change that distribution. We analyze the sensitivity of a proposed blind detection method based on the Giannakis-Tsatsanis Gaussianity test to evaluate the presence of narrowband and wideband non-Gaussian interference. Robustness of the proposed method to the blind-spot effect that occurs in pulsed interference signals is also discussed.